The analysis of 18F‐FDG PET/MRI, electroencephalography, and semiology in patients with gray matter heterotopia: A pilot study. (14th September 2022) - Alis, Ceren; Alis, Deniz; Uslu Besli, Lebriz; Karaarslan, Ercan; Sonmezoglu, Kerim; Ozkara, Cigdem; Yeni, Seher Naz
Abstract : Objectives: To describe 18 F‐fluorodeoxyglucose positron emission tomography/magnetic resonance imaging ( 18 F‐FDG PET/MRI) along with semiology and electroencephalography (EEG) in patients with gray matter heterotopia (GMH); to evaluate the concordance between 18 F‐FDG PET/MRI and clinical epileptogenic zone (EZ). Materials & Methods: GMH (subcortical heterotopia [SCH] and periventricular nodular heterotopia [PNH]) patients with epilepsy who underwent 18 F‐FDG PET/MRI were retrospectively enrolled. Two radiologists evaluated brain MRI, while two nuclear medicine specialists assessed the 18 F‐FDG PET. The SUVmax values of visually hypometabolic cortical areas were compared to the contralateral cortex using a SUVmax threshold value of 10%; the SUVmax values of GMH lesions were compared with that of the right precentral gyrus. The cortex or GMH with hypometabolism on 18 F‐FDG PET/MRI was considered representative of the EZ. The clinical EZ was identified using EEG and semiology. Results: Thirty patients (19 PNH; 11 SCH) with a mean age of 28.46 ± 9.52 years were enrolled. The heterotopic nodules were ametabolic in 3 patients (10%), hypometabolic in 16 (33.33%), isometabolic in 13 (26.66%), and hypermetabolic in 4 (10%). 18 F‐FDG PET/MRI demonstrated hypometabolism in the cortex and GMH in 22/30 (73.33%) and 16/30 (53.33%). We could identify a clinical EZ in 18 patients, and 15 out of 18 (83.33%) had concordant 18 F‐FDG PET/MRI findings. Conclusion: Heterotopic nodules in GMH patients show different metabolic patterns on 18 F‐FDG PET/MRI, with nearly three‐quarters of the patients having cortical hypometabolism. 18 F‐FDG PET/ MRI findings are mostly concordant with the clinical EZ.